Pengaruh Metode Pembelajaran Daring dan Minat Belajar terhadap Prestasi Belajar Mahasiswa di Perguruan Tinggi - Candra Abdillah; Dameis Surya Anggara (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The purpose of the study was to determine differences in student achievement using synchronous and asynchronous online learning methods, differences in student achievement with high learning interest and, as well as the effect of the interaction between learning factors and interest factors on student achievement in fifth semester, Economics Education Study Program, Pamulang University. The research approach uses a quantitative methodology with Quasi Experimental Type 2 x 2 Factorial Design. The data collection instruments are in the form of questions and questionnaires on learning interest. Data analysis using Two Way Anova with the condition that it is normally distributed and has homogeneous variance. The results of the study are: 1) There is a significant difference between the average learning achievement of students who apply synchronous and asynchronous methods with the details of student achievement who apply the synchronous method is higher than those who apply the asynchronous method for students who have high interest in learning, and student achievement those who apply the synchronous method are higher than those who apply the asynchronous method for students who have low interest in learning. 2) There is a significant difference between the learning achievement of students who have high and low learning achievement with details of student achievement with interest in learning better than those with low interest in learning compared to interest in learning. Low for implementation of asynchronous methods. 3) There is a significant interaction effect between learning method factors and learning interest on learning achievement in fifth semester students, Economics Education Study Program, Pamulang University